Antimicrobial activity of LysSS, a novel phage endolysin, against Acinetobacter baumannii and Pseudomonas aeruginosa. (September 2020) - Kim, Shukho; Lee, Da-Won; Jin, Jong-Sook; Kim, Jungmin
Highlights: LysSS endolysin belongs to the lysin and lysozyme family of Salmonella Typhimurium and Escherichia coli . LysSS has bactericidal effects on Acinetobacter baumannii and Pseudomonas aeruginosa . LysSS has no cytotoxic effect on A549 human lung cells. Intraperitoneal injection of LysSS protects mouse systemically infected with A. baumannii. Abstract: Objectives: Multidrug-resistant (MDR) bacteria are a major public-health concern. Bacteriophage endolysins (lysins) can be used as novel antimicrobial agents against bacterial infections. In this study, a novel endolysin (LysSS) containing a lysozyme-like domain was evaluated for its antibacterial activity against various species of bacteria. Methods: The LysSS-encoding gene was analyzed and cloned and the LysSS recombinant protein was expressed and purified. Purified LysSS was used to determine its antimicrobial activity against various bacterial species in vitro and to measure its protection rate against Acinetobacter baumannii systemic infection in an in vivo murine model. Results: Recombinant LysSS showed activity against MDR A. baumannii, MDR Escherichia coli, MDR Klebsiella pneumoniae, MDR Pseudomonas aeruginosa and Salmonella sp. without pre-treatment with an outer membrane permeabiliser. Moreover, LysSS inhibited the growth of methicillin-resistant Staphylococcus aureus (MRSA). The minimum inhibitory concentration (MIC) of LysSS against 16 MDR A. baumannii strains ranged from 0.063–0.25 mg/mL. LysSS had no cytotoxic effect on A549 human lung cells below 250 μg/mL. In an animal model, mice infected with A. baumannii were protected (40% survival rate with 125 μg LysSS) by intraperitoneal injection of LysSS. Conclusion: The current results demonstrate that LysSS may be a novel and promising antimicrobial agent against MRSA and MDR Gram-negative bacteria, including A. baumannii and P. aeruginosa .